Social distancing and social work field placements - Tedam, Prospera (The Journal of Practice Teaching and Learning, 2020)
The impact of the Coronavirus (COVID-19) pandemic on social work practice placements around the world and in the United Arab Emirates is of concern to students, social work educators and service users. In this practice note, I focus on the impact of the interruption to social work practice learning for students at the United Arab Emirates University and reflect on the introduction of 'social distancing', a health and safety strategy aimed at reducing the likelihood of the spread of the coronavirus. I propose ways in which students in school placements can continue to develop their social work knowledge and skills ‘from a distance’ and while physically absent from their practice learning settings